Investigating the nexus between natural resources, economic freedom, and financial development in Sub-Saharan Africa: an evidence from a dynamic panel threshold approach - Ali Gutale, Ali Abdulkadir; Bani, Yasmin; Abdul Samad, Abdul Rahim; Mohammad Afandi, Syamsul Herman (Springer, 2025)
In the face of global economic challenges, understanding the relationship between natural resources and financial development is crucial for sustainable development. Sub-Saharan Africa is abundant in natural resources, yet institutional weaknesses frequently limit its potential. This situation enables us to analyse how economic freedom could leverage these resources to enhance financial development. This study explores the nexus between natural resources (NR), economic freedom (EF), and financial development (FD) in Sub-Saharan Africa (SSA). Utilising a Dynamic Panel Threshold (DPT) estimator across 33 countries from 2005 to 2021, an EF threshold of 0.804 is identified. Below this threshold, NR negatively impacts FD, indicating a Financial Resource Curse (FRC) due to weak economic institutions. However, when EF exceeds this level, the curse dissipates, allowing NR to foster FD. Our findings, supported by robust testing through Method of Moments Quantile Regression (MMQR) and system Generalised Method of Moments (GMM) estimators, highlight the critical need for policymakers to invest NR revenues in institutional development. By doing so, SSA can transform resource wealth into a catalyst for financial development and economic prosperity.